Environmental Factors Modifying HDL Functionality - Kosmas, Constantine E.; Sourlas, Andreas; Guzman, Eliscer; Kostara, Christina E. (Current Medicinal Chemistry, 2022)
Background: Currently, it has been recognized that High-Density Lipoprotein (HDL) functionality plays a much more essential role in protection from atherosclerosis than circulating HDLcholesterol (HDL-C) levels per se. Cholesterol efflux capacity (CEC) from macrophages to HDL has been shown to be a key metric of HDL functionality. Thus, quantitative assessment of CEC may be an important tool for the evaluation of HDL functionality, as improvement of HDL function may lead to a reduction of the risk for Cardiovascular disease (CVD). Introduction: Although the cardioprotective action of HDLs is exerted mainly through their involvement in the reverse cholesterol transport (RCT) pathway, HDLs have also important anti-inflammatory, antioxidant, antiaggregatory and anticoagulant properties that contribute to their favorable cardiovascular effects. Certain genetic, pathophysiologic, disease states and environmental conditions may influence the cardioprotective effects of HDL either by inducing modifications in lipidome and/or protein composition, or in the enzymes responsible for HDL metabolism. On the other hand, certain healthy habits or pharmacologic interventions may actually favorably affect HDL functionality. Methods: The present review discusses the effects of environmental factors, including obesity, smoking, alcohol consumption, dietary habits, various pharmacologic interventions, as well as aerobic exercise, on HDL functionality. Results: Experimental and clinical studies or pharmacological interventions support the impact of these environmental factors in the modification of HDL functionality, although the involved mechanisms are not fully understood. Conclusion: Further research should be conducted to identify the underlying mechanisms of these environmental factors and to identify new pharmacologic interventions capable of enhancing CEC, improving HDL functionality and potentially improving cardiovascular risk.
Keywords: alcohol